Soccer Game Optimization: Fundamental Concept - Purnomo, Hindriyanto Dwi (Jurnal Sistem Komputer, 2014)
Optimization is important in science, engineering, economic as well as daily problems. The number of optimization methods increase continuously due to the growing optimization problems. In this study, we discussed the fundamental concept of soccer game optimization (SGO), a new algorithm inspired by the soccer player movements. The method consists of two basic movements; the move off and the move forward, to control the diversification and intensification and a player substitution procedure to keep the good solution during the search. The SGO elaborates the competition and the reproduction process in evolutionary algorithm with the powerful information sharing of swarm intelligence algorithm. As a new method, the SGO can be enhanced in many different ways such as elaborating more aspects of the soccer players’ movement as well as implementing the proposed method to solve various optimization problems